Molecular symmetry effects on the stability of highly ordered smectic phases. Issue 1 (2nd January 2019) - Ester, David F.; Williams, Vance E.
ABSTRACT: In an effort to control the phase ranges of highly ordered smectic phases, we examined the impact of molecular symmetry on phase behaviour of a series of 12 symmetrical and unsymmetrical 4, 4′-dialkanoyloxybiphenyl derivatives. Combined differential scanning calorimetry, polarised optical microscopy, and X-ray diffraction studies indicated that the compounds studied formed smectic F liquid crystals, and in some cases, G phases at lower temperatures. Although the clearing temperatures were largely unaffected by molecular symmetry, the transitions from the SmF liquid crystals to more ordered phases were consistently lowered upon reducing the molecular symmetry. As a result, unsymmetrical molecules had broader mesophases than their higher symmetry isomers, suggesting a strategy for tuning the phase behaviour of these highly ordered lamellar phases, which have been widely targeted for organic semiconductors. Graphical Abstract: